2012
DOI: 10.4236/ce.2012.32038
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation into Critical Thinking Skills of Urban High School Students: Role of an IT/STEM Program

Abstract: This paper reports the development of critical thinking of urban high school students in an IT/STEM program-using information technology (IT) within the context of science, technology, engineering, and mathematics (STEM). The study used a quasi-experimental time-series design, involving 47 initial participants in an eighteen-month intervention period. Data were collected from the Test of Everyday Reasoning (TER), which provides an overall score on critical thinking skill (CTS) and five sub-scale scores (analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 14 publications
3
45
0
9
Order By: Relevance
“…Duran, Höft, Lawson, Medjahed, and Orady () noted a similar pattern in another out‐of‐school education program. Because attendance was voluntary, student interest and motivation toward STEM fields were already high at the beginning of the program (Duran & Sendag, ). Similar to research findings in the present study, other investigations have noted significant increases in student attitudes toward STEM and STEM careers after attending STEM education programs (e.g., Duran & Sendag, ; Guzey et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duran, Höft, Lawson, Medjahed, and Orady () noted a similar pattern in another out‐of‐school education program. Because attendance was voluntary, student interest and motivation toward STEM fields were already high at the beginning of the program (Duran & Sendag, ). Similar to research findings in the present study, other investigations have noted significant increases in student attitudes toward STEM and STEM careers after attending STEM education programs (e.g., Duran & Sendag, ; Guzey et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because attendance was voluntary, student interest and motivation toward STEM fields were already high at the beginning of the program (Duran & Sendag, ). Similar to research findings in the present study, other investigations have noted significant increases in student attitudes toward STEM and STEM careers after attending STEM education programs (e.g., Duran & Sendag, ; Guzey et al, ). However, while this study showed a significant increase in student attitudes toward science and engineering, there was no significant improvement in student attitude toward mathematics and its relationship to STEM, and learning and use of technology.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, science, technology, engineering and mathematics disciplines play a significant role in developing these twenty first century skills [1,4,24]. Gaining these skills is also important for making decisions in social, economic and political issues [24].It is noted that students trained with STEM education grow up to be problem solver, innovative, self-confident, logically thinker, science and technology author-reader individuals and those STEM programs using information technologies contribute the development of critical thinking skills of students [16]. However, students lacking STEM skills could not head towards science and engineering related professions or disciplines that require literacy in mathematics, science and technology [7].…”
Section: Introductionmentioning
confidence: 99%
“…Focus on PBLs emphasizing critical thinking and reasoning skills yielded positive results in student achievement. In addition, students who experienced fun and excitement with science and robotics in shared communities of peer learners increased their interest and attitudes (Duran & Sendag, 2012).…”
Section: Methodology Participants and Settingmentioning
confidence: 99%